In vitro evaluation of methylglyoxal as an antibacterial additive to bone cement - Bohn, Maja Charlotte; Oltmanns, Hilke; Meißner, Jessica (Frontiers in Bioengineering and Biotechnology, 2025)
Periprosthetic joint infections (PJIs) are severe complications following surgical joint replacement and one of the main reasons for implant failure in human and veterinary medicine. Due to the global rise in antibiotic resistances and failure to prevent and treat PJIs, it is necessary to identify new antibacterial substances for the management of these infections. Methylglyoxal (MGO) is a dicarbonyl compound that has been identified as the main antibacterial component in Manuka honey. The aim of the study was to evaluate the suitability of MGO as an additive to polymethylmethacrylate bone cement in connection to PJIs. To test the antibacterial activity of pure MGO and MGO-containing bone cement against clinical isolates of Staphylococcus (S.) pseudintermedius, minimal inhibitory concentrations (MICs) were determined, growth of bacteria on bone cement was visualized, and the influence on infection of human osteosarcoma (HOS) cells was examined. Cytotoxicity of pure MGO and MGO-containing bone cement against HOS cells was analyzed with viability and proliferation assays, staining of cells on bone cement surface, and measurement of Interleukin-6 (IL-6) release. Activation of p38 MAP kinase was analyzed using Western blotting. MGO inhibited growth of S. pseudintermedius at 0.15 mg/mL, reduced bacterial colonization of bone cement at 25 mg per bone cement platelet, and reduced infection of HOS cells at 0.05 mg/mL. The IC50 of pure MGO for cell viability was 0.17 mg/mL. At higher concentrations, bone cement with MGO reduced viability and proliferation, but did not cause IL-6 release. Western blots revealed p38 activation following MGO treatment, indicating involvement of the p38 pathway in stress reactions due to the treatment. Taken together, effectiveness of MGO against PJI-relevant S. pseudintermedius could be shown but biocompatibility was limited and further research is necessary to enhance biocompatibility.